-(x-4)+2=13

Simple and best practice solution for -(x-4)+2=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(x-4)+2=13 equation:


Simplifying
-1(x + -4) + 2 = 13

Reorder the terms:
-1(-4 + x) + 2 = 13
(-4 * -1 + x * -1) + 2 = 13
(4 + -1x) + 2 = 13

Reorder the terms:
4 + 2 + -1x = 13

Combine like terms: 4 + 2 = 6
6 + -1x = 13

Solving
6 + -1x = 13

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -1x = 13 + -6

Combine like terms: 6 + -6 = 0
0 + -1x = 13 + -6
-1x = 13 + -6

Combine like terms: 13 + -6 = 7
-1x = 7

Divide each side by '-1'.
x = -7

Simplifying
x = -7

See similar equations:

| 4x^2-11x+8=6x+4 | | (6x-3)2=(4x+7)3 | | 3x=5(x-6) | | 27+u=3-3u | | 2(5+x)=150 | | 7-1x=4+x | | x^4-9x^3+27x^2-15x-52=0 | | X=45-4x | | 7-x+2=2x-12 | | 9x^2+17=71 | | 0=8t | | -x^2+9x=18 | | 6x^2-12x=-1 | | -7x=2x+3 | | 3m-2=-5m+9 | | x-8.8=-6.9 | | -6x+24=18 | | 15X+100000=14x+200000 | | 2b+6a=14 | | 4(x)-24=-20 | | 3(x-3)=-6 | | -x^2+11x=18 | | 3a+4b-5c=0 | | 4k^2+12k+9=0 | | -5x+17=-2x-4 | | p+31=13 | | 9v-5v=44 | | 3x-3=100 | | -2x+24=14 | | x+23=-14 | | -3x+1=-6x+2 | | Z^2+12z+36=0 |

Equations solver categories